Speaker Wars begins: Which applications will be the killer content for smart speaker? - Hyunmo Koo; Seongcheol Kim; Changi Nam (International Telecommunications Society (ITS), 2017)
Smart speakers have become next big thing in IoT industry. However, there is not enough discussion about which application would be killer content in smart speaker market. To boost market participation and the growth of the market, there should be a research predicting killer service in the smart speaker. This study uses an AHP model and framework to assess the priority for applications in smart speakers. This study compares three types of applications – Music, News, E-commerce – to investigate the priority.
Keywords: 330; smart speaker; artificial intelligence speaker; AHP; IoT